Silymarin inhibits the development of diet-induced hypercholesterolemia in rats - Krecman, V; Skottová, N; Walterová, D; Ulrichová, J; Simánek, V (Planta medica, 1998)
To study the ability of silymarin, a standardized mixture of antioxidant flavonolignans from the medicinal plant Silybum marianum, and of silybin, the main flavonolignan of silymarin, to inhibit the development of diet-induced hypercholesterolemia the rats were fed high cholesterol diet (HCD). Silymarin or silybin were given as dietary supplements, and their influences on serum cholesterol levels were compared to those of probucol, an antioxidant hypocholesterolemic drug. Anticholesterolemic effect of silymarin was parallel to that of probucol, and dose-dependent at dietary drug concentrations of 0.1-0.5-1.0% (w/w). However, in contradistinction to probucol, silymarin caused an increase in high density lipoprotein (HDL)-cholesterol and a decrease in liver cholesterol content, changes considered to be of benefit. In addition to its anticholesterolemic effect silymarin partially prevented the HCD-induced decrease in liver reduced glutathione, an endogenous antioxidant. Silybin was not so effective as silymarin suggesting that either other constituent(s) of silymarin may be responsible for its anticholesterolemic effect or the bioavailability of silybin alone might be lower than that of silybin as a compound of silymarin.
Keywords: Silymarin; Probucol; Rats, Wistar; HDL-cholesterol; Hypercholesterolemia; hypercholesterolemie; Cholesterol, HDL; cholesterol dietní; probukol; Cholesterol; Cholesterol, Dietary; potkani Wistar; silymarin; krysa rodu Rattus; glutathion; cholesterol; Animals; ženské pohlaví; játra; anticholesteremika; zvířata; Rats; peroxidace lipidů; Glutathione; Anticholesteremic Agents; Lipid Peroxidation; Liver; Female